2006
DOI: 10.1177/0959354306064278
|View full text |Cite
|
Sign up to set email alerts
|

Theory in Action

Abstract: Although the value placed on theoretical work in psychology has diminished over recent years, new and significant challenges to the status of theory have emerged within the intellectual community more generally. The demise of the mapping metaphor, the reduction of reason to rhetoric, and the recognition of the impossibility of value-neutral theorizing all raise questions concerning the status and function of theory. Critical theory in psychology has provided one response to these issues by employing theory as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 14 publications
0
20
0
1
Order By: Relevance
“…Adoption personnel and policymakers have much to learn from the experiences of lesbian women who are in the process of adopting. In this way, this research has the potential to move beyond exploratory understanding of lesbians' experiences into the realm of social action (Gergen & Zielke, 2006). While elucidating lesbian women's experiences is important, it is critical that this elucidation guide social change so that institutional and social forms of discrimination can be ameliorated.…”
mentioning
confidence: 99%
“…Adoption personnel and policymakers have much to learn from the experiences of lesbian women who are in the process of adopting. In this way, this research has the potential to move beyond exploratory understanding of lesbians' experiences into the realm of social action (Gergen & Zielke, 2006). While elucidating lesbian women's experiences is important, it is critical that this elucidation guide social change so that institutional and social forms of discrimination can be ameliorated.…”
mentioning
confidence: 99%
“…The use of Discursive Psychology has revealed that multiple and contrasting narratives of sexuality circulate in social spheres (Gergen & Zielke, 2006). This concurs with Speer and Potter (2000), who found multiple discourses of sexuality used in various social situations but contrasts with much of the previous research which has suggested pathologised and stable attitudes (for example, Ben Ari, 2001).…”
Section: Implications For Practice and Suggestions For Future Researchmentioning
confidence: 80%
“…In 2006, Theory & Psychology issued a special section called "Theory in Action," which focused on the topic of how theoretical psychology could act (Gergen & Zielke, 2006). Indeed, "Nothing is more practical than a good theory" (Lewin, 1951, p.169).…”
Section: Bridging the Gap Between Psychology And The Publicmentioning
confidence: 98%